Risk of subsidiaries of foreign banks in Indonesia: Impacts of the parent bank economic condition / Etikah Karyani ...[et al.] - -, Etikah Karyani; -, Adhinda Ghinna; -, Grace Ester; -, Meta Yulianti; -, Pricilia Adriana; -, Rafida Alifa (UiTM Cawangan Johor, 2019)
In this study, we investigated the influences of the parent bank condition on the total risk of foreign banks in Indonesia. We concentrated on the international transmission of accounting risk through the internal capital market of multinational banks. Accounting risk (total risk) is measured by the standard deviation of return on assets. Our results suggest that the total risk of the parent bank has influence on the subsidiaries’ total risk. We suggest these results indicate a new channel of international risk transfer from parent bank countries to host countries through foreign-owned banks.